Treatment options for irreparable postero-superior cuff tears in young patients - Galasso, Olimpio (World J Orthop, 2015)
Rotator cuff tears (RCTs) occur more commonly with advanced age, with most rotator cuff abnormalities in patients less than 30 years old being painful tendinoses or partial-thickness RCTs. Irreparable postero-superior cuff tears has been reported as frequent as 7% to 10% in the general population, and the incidence of irreparable RCTs in young patients is still unknown. Several surgical procedures have been proposed for young patients with irreparable postero-superior RCTs, such as rotator cuff debridement, partial rotator cuff repair, biceps tenotomy/tenodesis, rotator cuff grafting, latissimus dorsi tendon transfer, and reverse shoulder arthroplasty. After being thoroughly investigated in open surgery, arthroscopic techniques for latissimus dorsi tendon transfer have been recently described. They have been shown to be an adequate option to open surgery for managing irreparable postero-superior RCTs refractory to conservative management.